2020
DOI: 10.3390/antiox9060500
|View full text |Cite
|
Sign up to set email alerts
|

Copper Sources for Sod1 Activation

Abstract: Copper ions (i.e., copper) are a critical part of several cellular processes, but tight regulation of copper levels and trafficking are required to keep the cell protected from this highly reactive transition metal. Cu, Zn superoxide dismutase (Sod1) protects the cell from the accumulation of radical oxygen species by way of the redox cycling activity of copper in its catalytic center. Multiple posttranslational modification events, including copper incorporation, are reliant on the copper chaperone for Sod1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 110 publications
0
16
0
Order By: Relevance
“…On the other hand, we found that 25 µM D-Pen had little effect on the downstream signaling pathways. The maintenance of cell homeostasis may be a key factor in determining the related proteins of the signaling pathway (Sun et al, 2010;Galano et al, 2015;Boyd et al, 2020). Although the MTT results did not show the effect of D-Pen on the cells survival, the activity of LDH increased and the activity of SOD decreased in the 25 µM D-Pen medium (data not shown).…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, we found that 25 µM D-Pen had little effect on the downstream signaling pathways. The maintenance of cell homeostasis may be a key factor in determining the related proteins of the signaling pathway (Sun et al, 2010;Galano et al, 2015;Boyd et al, 2020). Although the MTT results did not show the effect of D-Pen on the cells survival, the activity of LDH increased and the activity of SOD decreased in the 25 µM D-Pen medium (data not shown).…”
Section: Discussionmentioning
confidence: 91%
“…Alternatively, since copper is a known cofactor for the copper/zinc superoxide dismutase 1 (SOD1), an enzyme involved in protecting the cells from reactive species produced during cellular respiration, 28–30 copper might have increased the cellular antioxidant defense capacity in a similar manner as it was suggested for manganese, 12 leading to an increased cell growth and fusion protein production. SOD1 is preventing cellular lipid peroxidation and deoxyribonucleic acid (DNA) damages by dismutating superoxide anions and is thus an essential enzyme of the cellular antioxidant defense system 30 …”
Section: Discussionmentioning
confidence: 99%
“…It has the largest kcat/KM of any known enzyme (≈7 × 10 9 M −1 s −1 ) and retains its activity in a wide range of pH and temperature values [ 87 ]. The level of active holo-SOD1 is backed up by the presence of a permanent apo-SOD1 pool, which can be converted to holo-SOD by transferring a copper ion from the Cu(I)-chaperone to SOD1 (CCS) that obtains copper directly from CTR1 at the cell membrane [ 88 , 89 ]. Thus, damping the activity of SOD1 is not an easy task.…”
Section: The Points In Which Iav-induced Inflammation Cross With Copper Metabolismmentioning
confidence: 99%